2022
DOI: 10.1111/ijfs.15728
|View full text |Cite
|
Sign up to set email alerts
|

Utilising grape juice processing by‐products as bulking and colouring agent in white chocolate

Abstract: In this study, grape pomace (mixture of grape seeds and skins) powder (GPP), obtained from grape processing, was used at different concentrations [10.0 (GPP10), 20.0 (GPP10) and 30.0 (GPP10) g/100 g] in white chocolate formulation for the partial replacement of sucrose. The results indicated that GPP addition at a higher concentration (>10.0 g/100 g) significantly affected the particle size, moisture content, texture and flow behaviour of white chocolate samples (P < 0.05). However, using GPP at a concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Results indicated that chocolate with added blackberry juice encapsulates (80 g/kg) had significantly higher polyphenolic content (145.86 g/100 g) compared to control chocolate (40.75 g/100 g), while pleasant fruity flavor and reduced sweetness improved the sensory attributes of chocolate with encapsulates. Furthermore, usage of grape seed powder extract resulted in a higher polyphenol bioavailability when grape-powder-enriched white chocolate (in saliva = 31.8 mg/kg; in gastric juice = 130.9 mg/kg; in intestinal juice = 154.2 mg/kg) was in vitro digested compared to control (in saliva = 0.38 mg/kg; in gastric juice = 195.1 mg/kg; in intestinal juice = 154.2 mg/kg) [ 41 ]. However, to the best of our knowledge, usage of winemaking by-products as polyphenol carriers in cocoa spread has not been studied before.…”
Section: Resultsmentioning
confidence: 99%
“…Results indicated that chocolate with added blackberry juice encapsulates (80 g/kg) had significantly higher polyphenolic content (145.86 g/100 g) compared to control chocolate (40.75 g/100 g), while pleasant fruity flavor and reduced sweetness improved the sensory attributes of chocolate with encapsulates. Furthermore, usage of grape seed powder extract resulted in a higher polyphenol bioavailability when grape-powder-enriched white chocolate (in saliva = 31.8 mg/kg; in gastric juice = 130.9 mg/kg; in intestinal juice = 154.2 mg/kg) was in vitro digested compared to control (in saliva = 0.38 mg/kg; in gastric juice = 195.1 mg/kg; in intestinal juice = 154.2 mg/kg) [ 41 ]. However, to the best of our knowledge, usage of winemaking by-products as polyphenol carriers in cocoa spread has not been studied before.…”
Section: Resultsmentioning
confidence: 99%
“…Didar [5] used free and encapsulated pomegranate extract to enhance the functionality of white chocolate in terms of antioxidant activity. Altınok et al [6] utilized grape pomace powder in white chocolate formulation for the partial replacement of sucrose.…”
Section: Introductionmentioning
confidence: 99%